Food immunotherapy practice: Nation differences across Europe, The FIND project - AYDINER, ELİF (WILEY, 2022)
Background Food allergen immunotherapy (FA-AIT) practice is known to vary globally. This project aims to identify and characterize European centres performing FA-AIT. Methods An EAACI task force conducted an online survey to gather relevant information regarding FA-AIT practice and setting-specific resources after reviewing the published literature and congress abstracts throughout Europe. Results We identified 102 FA-AIT centres in 18 countries; only Spain (n = 39) and France (n = 16) had >= 10 such centres. Overall, most facilities were hospital-based (77.5%), publicly funded (80.4%) and delivered FA-AIT as routine clinical care (80.4%). On average, departments had 3 allergists/paediatric allergists and 2 nurses. Surveyed centres had provided FA-AIT for a median of 9 years [1-24] to a median of 105 [5-2415] patients. The estimated total number of treated patients was 24875, of whom 41.3% received AIT for milk, 34.2% egg, 12.8% peanut and 11.7% other foods. Anaphylaxis to AIT doses requiring over 4-6 h of observation was reported by 70.6% of centres, ICU admissions by 10.8% and eosinophilic esophagitis by 45.1%. Quality of life and sustained unresponsiveness were evaluated in 20.6% and 54.9% of centres, respectively. The main contraindications for food AIT were severe asthma (57%-63%), eosinophilic esophagitis (56%-48%) and age below 5 years (47%-41%). Conclusions In Europe, FA-AIT is provided mostly in clinical practice. Significant variation is seen in the number of centres per country, facility characteristics and inclusion/exclusion criteria, and in certain aspects of protocols. Potential inequality in access to AIT has been identified as well as the need for education and guidance for treatment standardization.
Keywords: allergy; egg; food immunotherapy; milk; peanut; ORAL IMMUNOTHERAPY; ALLERGEN IMMUNOTHERAPY; PEANUT ALLERGY; CHILDREN; DESENSITIZATION; MILK; CONTRAINDICATIONS; GUIDELINES; EFFICACY; READY